Pengaruh Orientasi Kewirausahaan dan Kemampuan Pemasaran terhadap Kinerja Pemasaran UMKM Kuliner Pontianak - Ariadi; Febiwenesya Forever (BJRM (Bongaya Journal of Research in Management), 2026)
In the city of Pontianak, there are various culinary SMEs, which are one of the attractions for tourists to visit Pontianak. This research was conducted to connect entrepreneurial orientation and marketing capability to the improvement of the performance of culinary SMEs, also known as tourist snacks. The population of this study consists of culinary MSME business owners in the city of Pontianak, with a sample of 100 respondents using explanatory research analysis techniques. Primary data were collected thru questionnaires and analyzed using the SEM-PLS model. This study found that entrepreneurial orientation has a direct positive impact on marketing capability, and marketing capability also has a direct positive relationship with the marketing performance of culinary MSME products. Conversely, entrepreneurial orientation does not have a direct impact on marketing performance. One important factor in mediation is the marketing capability to balance entrepreneurial orientation with the marketing performance of culinary MSME products in the city of Pontianak.